PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN SIKKA - Emilianus Eo Kutu Goo (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
The purpose of this study is to analyze the effect of human resource competence and internal control systems on the quality of financial reports of the Sikka district government. The variables in this study are the independent variable (X) consisting of human resource competence (X1) and the internal control system (X2) and the dependent variable (Y) is the quality of local government financial reports.This type of research is an empirical study. Data collection was carried out by distributing 50 questionnaires filled in by respondents who are staff at the Regional Finance Agency of Sikka Regency. The data obtained were analyzed using descriptive statistical tests, validity tests, reliability tests and classical assumption tests.The results showed that there was no relationship or no influence between Human Resource Competence on the Quality of Regional Government Financial Reports and there was a relationship or influence between the Internal Control System on the Quality of Regional Government Financial Reports.